Bioinspired Gyrotropic Metamaterials with Multifarious Wave Adaptability and Multifunctionality. Issue 12 (15th April 2020) - Huang, Lingxi; Duan, Yuping; Liu, Jia; Zeng, Yuansong; Ma, Guojia; Pang, Huifang; Gao, Shaohua; Zhang, Weiping
Abstract: Electromagnetic wave loss caused by rotating polarization of chiral structures has long been considered as a disadvantage in transmission, detection, etc., however, it can be turned to benefit in microwave absorbing materials to enhance absorption. Herein, inspired by the chiral structure of jeweled beetles, gyrotropic metamaterials (MMs) are designed and prepared, and experimentally demonstrate the enhanced microwave absorption by rotating polarization; the bandwidth of absorptivity greater than 80% (reflection loss, RL ≤ −7 dB) covers the entire 4–18 GHz frequency range under an ultralow surface density of 1.45 kg m −2 ; the mechanism analyzed and verified by simulation models demonstrates this a universal method. A new paradigm of MMs fabricated by high entropy alloy (HEA) is offered in this work, which increases the freedom of MM design and promotes the integration of material science and physics. Multifarious wave adaptability and multifunctionality achieved by integrated HEA unit cell and foamed polyurethane realize ultrasonic and water wave absorption, as well as impact and corrosion resistance. These designs hold great promise for facilitating functionally integrated materials for stealth technology, antiterrorist, encryption, sensing, and photon detection. Abstract : Inspired by the chiral structure of jeweled beetles, gyrotropic microwave absorption metamaterials are designed and prepared, and experimentally demonstrate the enhanced microwave absorption by rotating polarization and also their multifarious wave adaptability and multifunctionality. A new paradigm of metamaterials fabricated by high entropy alloy is offered, which has great potential application in stealth devices of marine environment.